2016
DOI: 10.1002/ijc.30239
|View full text |Cite
|
Sign up to set email alerts
|

Risk of neuroblastoma, birth‐related characteristics, congenital malformations and perinatal exposures: A pooled analysis of the ESCALE and ESTELLE French studies (SFCE)

Abstract: Neuroblastoma (NB), an embryonic tumour arising from neural crest cells, is the most common malignancy among infants. The aetiology of NB is largely unknown. We conducted a pooled analysis to explore whether there is an association between NB and preconception and perinatal factors using data from two French national population-based case-control studies. The mothers of 357 NB cases and 1783 controls younger than 6 years, frequency-matched by age and gender, responded to a telephone interview that focused on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
1
18
1
Order By: Relevance
“…The distribution by study, age at diagnosis and malignancy status are shown in Supporting Information Table 1. In total, 437 (85.7%) of the tumours were malignant and 73 were nonmalignant, the majority of which were astrocytomas (51) or other gliomas (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution by study, age at diagnosis and malignancy status are shown in Supporting Information Table 1. In total, 437 (85.7%) of the tumours were malignant and 73 were nonmalignant, the majority of which were astrocytomas (51) or other gliomas (20).…”
Section: Resultsmentioning
confidence: 99%
“…Low folate levels at this time may be associated with increased DNA methylation, thereby suppressing expression of genes, such as OTX2, which are implicated in neural crest development in the critical first week following fertilisation. 17 While there may be a protective association between breastfeeding and childhood cancer overall, 18 acute lymphoblastic leukemia, 18,19 and neuroblastoma, 18,20 previous publications 19,[21][22][23][24] have found no such association with CBT. However, as other factors related to the early priming of the immune system, that is, allergy 25 and asthma, [25][26][27] have been associated with decreased risk, a protective association is still plausible.…”
mentioning
confidence: 95%
“…Increased risks for subsequent CNS, neuroblastoma, germ cell, and rhabdomyosarcoma tumors among children with congenital anomalies have been previously reported, as well as specific risks for those with a neurological, circulatory, genitourinary, digestive, and musculoskeletal abnormality (Agha et al, ; Altmann et al, ; Bjorge et al, ; Botto et al, ; Carozza et al, ; Fisher et al, ; Narod et al, ; Rios et al, ). However, few studies have provided specific anomaly/tumor subtype comparisons (Baptiste et al, ; Birch et al, ; Durmaz et al, ; Gold et al, ; Hall et al, ; Johnson, Annegers, Frankowski, Spitz, & Buffler, ; Rankin et al, ; Sun, Overvad, & Olsen, ).…”
Section: Discussionmentioning
confidence: 97%
“…Multiple linkage studies have reported a prevalence of 2–3% of children with congenital anomalies in the general population (Hoyert et al, ; Yoon et al, ). Several large‐scale epidemiologic studies have provided substantial evidence of an association between congenital anomalies and cancer risk in children (Agha et al, ; Altmann, Halliday, & Giles, ; Bjorge, Cnattingius, Lie, Tretli, & Engeland, ; Botto et al, ; Carozza, Langlois, Miller, & Canfield, ; Hall, Ritz, Cockburn, Davidson, & Heck, ; Janitz et al, ; Mili, Khoury et al, ); Narod, Hawkins, Robertson, & Stiller, ; Rankin, Silf, Pearce, Parker, & Ward Platt, ; Rios et al, ; Windham, Bjerkedal, & Langmark, ). Studies have demonstrated significant associations specifically between neurological congenital anomalies and pediatric cancer (Altmann et al, ; Bjorge et al, ; Botto et al, ; Carozza et al, ; Narod et al, ), with some suggesting a specific link between neurological malformations and central nervous system tumors (Agha et al, ; Altmann et al, ; Bjorge et al, ; Narod et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The ESCALE and ESTELLE studies were two separate nationwide population‐based case–control studies conducted by the same investigators in France. The study designs have been previously described elsewhere . Both studies included cases of NB, lymphoma, leukaemia and malignant brain tumour.…”
Section: Methodsmentioning
confidence: 99%